Effects of long-term tillage systems on aggregate-associated organic carbon in the eastern Mediterranean region of Turkey - Mert Acar; Ismail Celik; Hikmet Günal (Eurasian Journal of Soil Science, 2018)
The stability of aggregates plays a vital role in preserving and long term storing of soil organic carbon (SOC). In this study, the long-term (2006-2014) effects of six tillage systems on aggregate-associated SOC were investigated in a field experiment conducted under Mediterranean conditions. The tillage treatments were; conventional tillage with residue incorporated in the soil (CT1), conventional tillage with residue burned (CT2), reduced tillage with heavy tandem disc-harrow (RT1), reduced tillage with rotary tiller (RT2), reduced tillage with heavy tandem disc harrow fallowed by no-tillage (RNT) for the second crop, and no tillage (NT). The most frequently encountered aggregates in all tillage systems were at 4.0-2.0 mm size and the least frequently found aggregates were 1.0-0.5 mm. The mean weight diameter (MWD) value increased in the NT compared to the conventional tillage practices at the rates of 137% and 204%, respectively at 0-15 cm soil depth. Aggregate-associated SOC contents in 0-15 cm depth were higher under conservation tillage systems. However, the highest SOC at 15-30 cm depth were greater mainly in conventional tillage systems as 9.4% for both CT1 and CT2. The results indicated that conservation tillage systems had greater aggregation and carbon storage at the soil surface.